Transitivity Process In Bon Jovi's Selected Song Lyrics - Hiace Vega Fernando Siahaan (ITScience (Information Technology and Science), 2021)
The focus of this research is to find the usage of the transitivity processes in Bon Jovi’s selected song lyrics. This research is descriptive qualitative research. This research aims to discover and examine types of the transitivity processes used in Bon Jovi’s selected song lyrics. The source data of this research are the twenty selected song lyrics of Bon Jovi. Meanwhile, the data of this research are the clauses that used transitivity processes in Bon Jovi’s selected song lyrics. The data of this research are analyzed by using the interactive model. The result of this research shows that all of the six types of transitivity processes are found in Bon Jovi’s selected song lyrics, namely: material processes, mental processes, relational processes, verbal processes, behavioral processes, existential processes. It shows that Bon Jovi, in realizing the song, applied the six types of transitivity processes. From the six types of transitivity processes that are found, the material process is dominantly used in Bon Jovi’s selected song lyrics. It indicates that Bon Jovi’s selected song lyrics are related to the physical activity that happens in the social phenomena. It is helpful for the readers to know transitivity processes in understanding the message of the song. Besides it, it also gives advantages for the songwriter in writing song lyrics to provide the varieties of wording in the songs.